Urine and Serum Biomarkers of Cardiovascular Status and Early Vascular Ageing in Children and Adults - Mikaela Frixou; Catherine Fraser; Angela K. Lucas-Herald (Artery Research)
Abstract Given that cardiovascular disease remains the leading cause of morbidity and mortality worldwide, there is a need to identify biomarkers that are accurate and reproducible to be able to identify which individuals are most at risk of early vascular ageing (EVA) to then allow for prioritisation of interventions to reduce this risk. To date, a myriad of different urine and blood biomarkers have been reported in studies looking at cardiovascular risk and EVA. These biomarkers primarily focus on oxidative stress, inflammation, haemostasis and thrombosis, metabolic markers, cardiovascular injury and epigenetic changes. As such, this review seeks to summarise the most common blood and urine markers reported in the literature and their current reported uses. Reference data in both adult and paediatric populations remain elusive for many of these biomarkers and may also be dependent on the assays used for analysis. It is possible that multi-marker risk scores may be of increased utility in the diagnosis of EVA. In addition, advances in technology may change the landscape of biomarker discovery in future years, with a need to prioritise research in the field of EVA to reduce the worldwide cardiovascular disease burden.